2020
DOI: 10.3389/fbioe.2020.00926
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on Synthetic and Polysaccharide Adhesives for Biological Hemostatic Applications

Abstract: Rapid hemostasis and formation of stable blood clots are very important to prevent massive blood loss from the excessive bleeding for living body, but their own clotting process cannot be completed in time for effective hemostasis without the help of hemostatic materials. In general, traditionally suturing and stapling techniques for wound closure are prone to cause the additional damages to the tissues, activated inflammatory responses, short usage periods and inevitable second operations in clinical applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 128 publications
(166 reference statements)
0
37
0
Order By: Relevance
“…Many studies have shown various materials such as fibrin-/silk- [ 15 ], polysaccharide- [ 16 ], and collagen-based adhesives [ 17 ], which can be used as soft hydrogels for hemostasis. Collagen is one of the essential extracellular matrices in gingival tissues [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown various materials such as fibrin-/silk- [ 15 ], polysaccharide- [ 16 ], and collagen-based adhesives [ 17 ], which can be used as soft hydrogels for hemostasis. Collagen is one of the essential extracellular matrices in gingival tissues [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is a linear amino-polysaccharide with the backbone of β-(1–4)-linked D-glucosamine, which possesses favorable biocompatibility, biodegradability, high viscosity, and unique antibacterial property for bio-applications ( Yang et al, 2018 ; Li et al, 2020b ; Tang et al, 2020 ; Yang et al, 2021b ; Yang et al, 2021c ). However, its poor solubility in neutral pH requires the manufacturing process in acidic condition for bio-ink preparation, which greatly limits cell viability and proliferation, especially for the direct bioprinting.…”
Section: Polymer-based Bioprinting Hydrogels For Cartilage Tissue Engineeringmentioning
confidence: 99%
“…The reactive amino group of chitosan can be favorably modified for different applications. Research has established that modified chitosan can enhance hemostatic efficacy [49]. Nie et al, have developed a chitosan-based hydrogel adhesive sealant consisting of thiolated chitosan (CSS) and maleimide-modified Îľ-polylysine via Michael addition crosslinking, which indicated adhesive strengths of up to four times that of their non-functionalized un-crosslinked counterparts [50].…”
Section: Chitosanmentioning
confidence: 99%